2013
DOI: 10.4103/0019-509x.112307
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of female breast carcinoma: A case control study at Puducherry

Abstract: Nulliparity, past history of benign breast lesion, high fat diet and consumption of oils with more saturated fats were the risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 8 publications
4
39
0
5
Order By: Relevance
“…[1][2][3][4][5][6][7] Breast cancer is amongst the most common cancer in women both in the developed and the developing world whose incidence is increasing specially in the developing world due to increased life expectancy, increase urbanization and adoption of unhealthy stressful lifestyles. 8, 9 Age standardised incidence rate in India is about 25.8 per 100,000 women that is roughly 1 in 4000 are females affected.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Breast cancer is amongst the most common cancer in women both in the developed and the developing world whose incidence is increasing specially in the developing world due to increased life expectancy, increase urbanization and adoption of unhealthy stressful lifestyles. 8, 9 Age standardised incidence rate in India is about 25.8 per 100,000 women that is roughly 1 in 4000 are females affected.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bhadoria AS et al [10] reported 62.5% of their patients to be between 30-50 years with mean age of 45±10.29 years [10]. Balasubramaniam SM et al [11] also found 35.5% of their patients in the age group of 41-50 years with mean age of 49.1±10.85 years [11]. The average age of our breast cancer patients may be even lower, as most of our patients present in an advanced stage probably due to low level of awareness, cumbersome referral pathways and limited access to standard cancer care in the country [12].…”
Section: Discussionmentioning
confidence: 99%
“…educational status and history of benign breast disease in the family are consistent with the results of study by Hosseinzadeh et al (20), Braaten et al (24) and Cunningham et al (25) regarding the economic-social status (education level and income). The economic-social factors and life style factors like diet and physical activity can influence fertility behaviors such as infertility, age at first pregnancy, number of (32) and La Vecchia et al (33) regarding the diet (using oily foods, fruits and vegetables). Therefore increasing women's awareness and knowledge regarding early diagnosis is an essential (21).…”
Section: Discussionmentioning
confidence: 99%